Automatized systems for maintenance of air engine operation - Кулик, М. С.; Тарасенко, А. В. (Proceedings of National Aviation University (archive), 1999)
Considered are the problems of expedience of creation of automatized systems for maintenance of’air engine operation by aviation enterprises. Main principles of forming information for increasing of reliability and efficiency of air engine operation are suggested